Pathologic Complete Response to Neoadjuvant Nivolumab/Ipilimumab in a Patient with Metastatic Renal Cell Carcinoma - Taylor C. Peak; Elena M. Fenu; Michael B. Rothberg; Christopher Y. Thomas; Ronald L. Davis; Edward A. Levine (Case Reports in Urology)
Nivolumab plus ipilimumab represents an effective combination of checkpoint inhibitors that can lead to a durable response with minimal toxicity in patients with metastatic renal cell carcinoma (mRCC). We present a case of a pathologic complete response to neoadjuvant nivolumab plus ipilimumab in a patient with a 13.9 cm left renal mass and significant retroperitoneal and iliac lymphadenopathy, classified as intermediate-risk mRCC. We discuss and review the literature on complete responses after systemic therapy and the ability to predict who has undergone a complete response in the face of residual radiographic evidence of disease.